In Situ Electrodeposition of an Asymmetric Sol–Gel Membrane Based on an Octadecyltrimethoxysilane Langmuir Film. Issue 38 (8th August 2014) - Hitrik, Maria; Lev, Ovadia; Mandler, Daniel
Abstract The unique properties of Langmuir film formation were utilized in assembling a thin skin of an asymmetric membrane. An octadecyltrimethoxysilane (ODTMS) Langmuir monolayer was formed at the air–water interface and served as the substrate for growing a bulky sol–gel polymer in situ. The latter was based on the electrochemical deposition of tetramethoxysilane dissolved in the water subphase by means of horizontal touch electrochemistry. The resultant asymmetric layer that consisted of a thin hydrophobic ODTMS Langmuir film connected to a bulk hydrophilic sol–gel network was studied in situ and ex situ by using various techniques, such as cyclic voltammetry, electrochemical impedance spectroscopy (EIS), scanning electron microscopy, transmission electron microscopy (TEM), and goniometry. We found that a porous hydrophilic film grew on top of a hydrophobic layer as was evident from TEM, contact angle, and EIS analyses. The film thickness and film permeability could be controlled by changing the deposition conditions such as the potential window applied and its duration. Hence, this method offers an alternative approach for assembling asymmetric films for various applications